Perceived frailty and clinical outcomes in men and women with atrial fibrillation treated with edoxaban: insights from the 2-year follow-up of ETNA-AF-Europe. (3rd October 2022) - De Vries, T A C; Pecen, L; Komen, J J; Diemberger, I; Fumagalli, S; De Groot, J R; Kirchhof, P; De Caterina, R
Abstract: Background/Introduction: Many clinicians estimate the frailty of patients solely using their clinical expertise instead of validated scores. Previous reports show that women are more often perceived as frail than men. It is uncertain whether the same trend is observed in patients with atrial fibrillation (AF) and if the association between perceived frailty and adverse clinical outcomes is affected by sex. Purpose: To assess whether sex affects the association between frailty status and adverse clinical outcomes in patients with AF. Methods: ETNA-AF-Europe is an ongoing, post-authorisation, prospective cohort study conducted in 825 centres enrolling patients with AF treated with edoxaban in 10 European countries. In this substudy on the first 2-years of follow-up, patients were categorised in four subgroups based on sex and clinician-perceived frailty at baseline. We calculated incidence rates (per 100 patient-years) of the composite endpoint of any stroke or systemic embolic event (SEE), of major bleeding, and of all-cause death for the four subgroups; and determined the unadjusted association between perceived frailty (frail vs non-frail) and each outcome, stratified by sex, using Cox proportional hazards models. To assess for consistency in our findings, we tested the same associations by sex category but using objective risk factors: age (>74 vs <65 years) and CHA2DS2-VASc score (≥4 vs <4). Results: Information about frailty-status was recorded for 12, 254 (93.3%) patients, of whom 8.5% of men and 15.4% of women were perceived as frail by their clinician (p<0.0001) (Table 1). For both sex categories calculated separately, the risk of any stroke or SEE, major bleeding, or all-cause death was higher in the frail than in the non-frail patients (Figure 1A). However, the difference in risks of stroke or SEE between frail and non-frail patients was greater for men (HR 3.77, 95% confidence interval [CI] 2.25–6.31) than for women (HR 2.18, 95% CI 1.34–3.55) and a similar trend toward a greater risk-difference for men was seen for the risk of all-cause death (HR 4.58, 95% CI 3.76–5.59 vs HR 3.63, 95% CI 2.94–4.49). There was no marked difference between sex categories in the association between frailty-status and major bleeding (HR 2.86, 95% CI 1.81–4.50 vs HR 2.56, 95% CI 1.68–3.90) (Figure 1A). The association of age or CHA2DS2-VASc subgroups with clinical outcomes were either similar between sexes or suggested a possible lower risk-difference for men (Figure 1B and 1C). Conclusion: In our cohort, differences in the risks of clinical outcomes between those who were perceived as frail and those who were not is more pronounced for men than women. Because we did not observe similar trends in the associations between age or CHA2DS2-VASc score subgroups and clinical outcomes, our results indicate that clinicians perceive the extent of frailty differently in men than in women. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): This research was funded by Daiichi Sankyo Europe.